2013
DOI: 10.1111/j.1600-0587.2013.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate and vegetation hierarchically structure patterns of songbird distribution in the Canadian boreal region

Abstract: Environmental factors controlling the distribution and abundance of boreal avifauna are not fully understood, limiting our ability to predict the consequences of a changing climate and industrial development activities underway. We used a compilation of avian point-count data, collected over 1990 -2008 from nearly 36 000 locations, to model the abundance of individual forest songbird species within the Canadian boreal forest. We evaluated 30 vegetation and 101 climatic variables, representing most of the widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 92 publications
(141 reference statements)
4
42
0
Order By: Relevance
“…Furthermore, significant impacts of climate change are predicted to occur at boreal latitudes resulting in increased plant growth (infilling; Danby and Hik 2007) or increased recruitment in treeline species, and a subsequent migration of the treeline, latitudinally and altitudinally (Cannone et al 2007;Ruckstuhl et al 2008;Harsch et al 2009). The potential for changes in avian distribution in response to a changing climate was suggested by Cumming et al (2014), who showed that climate variables explained most of the deviance in abundance of boreal songbird distribution. An examination in the boreal region will broaden our understanding of the influence of ecotones on avian diversity and shed light on the influence of global climate change on these regions.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, significant impacts of climate change are predicted to occur at boreal latitudes resulting in increased plant growth (infilling; Danby and Hik 2007) or increased recruitment in treeline species, and a subsequent migration of the treeline, latitudinally and altitudinally (Cannone et al 2007;Ruckstuhl et al 2008;Harsch et al 2009). The potential for changes in avian distribution in response to a changing climate was suggested by Cumming et al (2014), who showed that climate variables explained most of the deviance in abundance of boreal songbird distribution. An examination in the boreal region will broaden our understanding of the influence of ecotones on avian diversity and shed light on the influence of global climate change on these regions.…”
Section: Introductionmentioning
confidence: 97%
“…The effects of habitat fragmentation and alteration remain unclear with studies reporting contrasting results. Cumming et al (2013) and Stralberg et al (in press) have shown that variation in CAWA abundance was best explained by the number of growing degree days (> 5°C and < 0°C). Although to a lesser extent, mean differences between the warmest and coldest monthly temperatures (climate), mean normalised difference vegetation index (NDVI), mean leaf area index (LAI; vegetation), compound topographic index, and the proportion of water bodies in 4-km grid cell (topographic) were also good predictors of variation in CAWA abundance.…”
Section: Focal Speciesmentioning
confidence: 99%
“…burns), but higher nesting success has been documented in burns (Robertson and Hutto 2007). According to Cumming et al (2013) and Stralberg et al (in press), variation in OSFL abundance across the continent was best explained by the mean and standard deviation of the mean maximum monthly temperature and to a lower extent by mean precipitation, number of degree days (> 5°C), climate moisture index, difference between mean warm month and cold month temperatures (climate) and LAI (vegetation). The Canadian breeding range for this species covers about 5,175,600 km 2 (http://www.natureserve.org/; Figure 3) including every Canadian province and territory except Nunavut (Table 1).…”
Section: Focal Speciesmentioning
confidence: 99%
“…When compared to southern non-montane boreal forest, bird species in forested habitats in our study are less abundant and bird communities are not as rich in similar habitats at the point-count scale (Machtans and Latour, 2003). This could be a result of climatic limitations on breeding phenology, lower structural heterogeneity of vegetation, and potentially lower prey abundance (Zhang et al, 2012;Cumming et al, 2014). In addition, Machtans and Latour (2003) used a point-count radius of only 50 m, in contrast to the unlimited distance point-count radius used in our study, which makes the reduced abundance and richness of birds found in our northern study area even more striking.…”
Section: Discussionmentioning
confidence: 61%